Cilostazol protective effect on nedaplatin-induced genotoxicity in cultured human lymphocytes - Karem H. Alzoubi; Abeer M. Rababa’h; Omar F. Khabour; Fian Nuseir (Toxicology Reports)
Background: Nedaplatin has demonstrated remarkable efficacy in combating various malignancies. However, the administration of nedaplatin has been associated with the induction of DNA damage within normal cells. Cilostazol is a phosphodiesterase III inhibitor with an antioxidant mechanism that could protect cells from genotoxicity. We aimed to evaluate the genotoxic effect of nedaplatin on cultured human lymphocytes and the potential protective effect of cilostazol on chromosomal damage induced by nedaplatin. Methods: The proposed nedaplatin’s genotoxic effect was studied in vitro by evaluating the frequencies of sister chromatid exchanges (SCEs) in human cultured lymphocytes. Both the mitotic and proliferative indices (MI and PI, respectively) were used to assess the cytotoxic effects of nedaplatin. Results: Nedaplatin significantly increased the frequency of SCEs compared to control and cilostazol-treated cells. The chromosomal injury induced by nedaplatin was significantly reduced by pretreatment of cells with cilostazol (P < 0.0001). Treating with cilostazol alone also reduced the frequency of SCEs, MI, and PI compared to the control group. Nedaplatin induced significant decreases in the MI and PI compared to the control group. Pretreatment with cilostazol partially debilitated the nedaplatin-induced changes in MI but not PI. Conclusion: Cilostazol ameliorated the genotoxicity of nedaplatin in cultured human lymphocytes.